Developing Business to Business Product Launches Corresponding to the Customer Acquisition Journey : Evaluation of the Process in a Case Company Context - Huhtala, Sofia Hilja Josefiina (My University, 2019)
The marketing environment has changed drastically causing B2B customers to evaluate, compare alternatives and seek more and more information by themselves in the digital environment without traditional intrusive marketing. Marketing has become more data-driven and measurable making it is easier to follow statistics and identify prospective customers better and lead them to the sales funnel. The importance of digitalisation and data has been understood as a means to improve the hit-rate and the quality of content and not only should companies digitalise the products but also the way products are being sold. The objective of this study is to evaluate how the case company can develop its product launches to correspond to the requirements of the digitalised marketing of today and to launch and control products and solutions more efficiently. The theoretical framework was based on literature and academic publications regarding B2B product marketing and inbound marketing practices which were combined to create a holistic perspective creating a successful product launch plan. To reach the research objective, a qualitative study was conducted to collect relevant data through interviews within the case company and combined with the data from the viewpoint of external customers. It is not possible to predict the future without data the thereby this matter needs to be comprehended more profoundly in B2B companies to adapt to the change in marketing and to better correspond to the digitalised needs. The findings of the study suggested that the internal roles need to be defined clearer, cooperation between internal stakeholders need to be strengthened, launch and campaign planning needs to be more efficient and clear measurement metrics need to be created for planning and executing product launches to flow more efficiently.
Keywords: B2B; Business to Business; Product Marketing; Product Launches; Inbound Marketing; fi=Tuotantotalous (KTK)|en=Industrial Management|; Master's Programme in Industrial Management; Logistics and Production Operations Management